Podpora vedení studentů na praxi v mateřské škole - Syslová, Zora (Masaryk University Press, 2019)
Title in English: Support of student leadership in kindergarten practice The methodological handbook theoretically anchors and argues reflective conceived preparatory education of kindergarten teachers, an integral part of which is the provision of mentoring support by accompanying teachers. The whole publication thus aims to understand the role of the accompanying teacher and its place in supporting the development of the teacher as a reflective practice.